Influence of skeletal muscle and intermuscular fat on postoperative complications and long‐term survival in rectal cancer patients - Tong Nie; Feihong Wu; Yixin Heng; Wentai Cai; Zhihao Liu; Le Qin; Yinghao Cao; Chuansheng Zheng (Wiley, 2024)
Abstract Background The body composition of patients with rectal cancer potentially affects postoperative outcomes. This study explored the correlations between skeletal muscle and adipose tissue quantified by computed tomography (CT) with postoperative complications and long‐term prognosis in patients with rectal cancer after surgical resection. Methods This retrospective cohort study included patients with rectal cancer who underwent surgical resection at the Wuhan Union Hospital between 2014 and 2018. CT images within 3 months prior to the surgery were used to quantify the indices of skeletal muscle and adipose tissue at the levels of the third lumbar vertebra (L3) and umbilicus. Optimal cut‐off values for each index were defined separately for males and females. Associations between body composition and postoperative complications, overall survival (OS), and disease‐free survival (DFS) were evaluated using logistic and Cox proportional hazards models. Results We included 415 patients (240 males and 175 females; mean age: 57.8 ± 10.5 years). At the L3 level, a high skeletal muscle density (SMD; hazard ratio [HR]: 0.357, 95% confidence interval [CI]: 0.191-0.665, P = 0.001; HR: 0.571, 95% CI: 0.329-0.993, P = 0.047) and a high skeletal muscle index (SMI; HR: 0.435, 95% CI 0.254-0.747, P = 0.003; HR: 0.568, 95% CI: 0.359-0.897, P = 0.015) were independent prognostic factors for better OS and DFS. At the umbilical level, a large intermuscular fat area (IMFA; HR: 1.904, 95% CI: 1.068-3.395, P = 0.029; HR: 2.064, 95% CI: 1.299-3.280, P = 0.002) was an independent predictive factor for worse OS and DFS, and a high SMI (HR: 0.261, 95% CI: 0.132-0.517, P < 0.001; HR: 0.595, 95% CI: 0.387-0.913, P = 0.018) was an independent prognostic factor for better OS and DFS. The models combining body composition and clinical indicators had good predictive abilities for OS. The receiver operating characteristic areas under the curve were 0.848 and 0.860 at the L3 and umbilical levels, respectively (both P < 0.05). Conclusions No correlations existed between CT‐quantified body composition parameters and postoperative complications. However, a high SMD and high SMI were significantly associated with longer OS and DFS at the L3 level, whereas a large IMFA and low SMI were associated with worse OS and DFS at the umbilical level. Combining CT‐quantified body composition and clinical indicators could help physicians predict the prognosis of patients with rectal cancer after surgery.